Trading master interview with Charles Faulkner : investing principles and trading techniques from a trend following master. - Covel, Michael W., 1968- (FT Press, 2010)
"Charles Faulkner is an American, currently living in England, who is a master NLP (Neuro-linguistic Programming) practitioner and trainer, life coach, motivational speaker, trader and author. Faulkner became a futures trader in the early 90's as a way to apply his NLP-based models for peak performance, a trend follower technique. He encouraged fellow traders who were breaking into the industry to use positive statements when journaling. Otherwise, a trader may wind up unconsciously setting in negative trading patterns. He discusses a more abstract than detailed way of following trends, taking into account anthropological and sociological observations, balanced with occasional specific insights. His approach often touches on counter-intuitive ways of making sense of trends."--Resource description page.